SARS-CoV-2 multi-variant rapid detector based on graphene transistor functionalized with an engineered dimeric ACE2 receptor. (February 2023) - Romagnoli, Alice; D'Agostino, Mattia; Pavoni, Eleonora; Ardiccioni, Chiara; Motta, Stefano; Crippa, Paolo; Biagetti, Giorgio; Notarstefano, Valentina; Rexha, Jesmina; Perta, Nunzio; Barocci, Simone; Costabile, Brianna K.; et al.
Abstract: Reliable point-of-care (POC) rapid tests are crucial to detect infection and contain the spread of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The emergence of several variants of concern (VOC) can reduce binding affinity to diagnostic antibodies, limiting the efficacy of the currently adopted tests, while showing unaltered or increased affinity for the host receptor, angiotensin converting enzyme 2 (ACE2). We present a graphene field-effect transistor (gFET) biosensor design, which exploits the Spike-ACE2 interaction, the crucial step for SARS-CoV-2 infection. Extensive computational analyses show that a chimeric ACE2-Fragment crystallizable (ACE2-Fc) construct mimics the native receptor dimeric conformation. ACE2-Fc functionalized gFET allows in vitro detection of the trimeric Spike protein, outperforming functionalization with a diagnostic antibody or with the soluble ACE2 portion, resulting in a sensitivity of 20 pg/mL. Our miniaturized POC biosensor successfully detects B.1.610 (pre-VOC), Alpha, Beta, Gamma, Delta, Omicron ( i.e., BA.1, BA.2, BA.4, BA.5, BA.2.75 and BQ.1) variants in isolated viruses and patient's clinical nasopharyngeal swabs. The biosensor reached a Limit Of Detection (LOD) of 65 cps/mL in swab specimens of Omicron BA.5. Our approach paves the way for a new and reusable class of highly sensitive, rapid and variant-robust SARS-CoV-2 detection systems. Graphical Abstract: We present a graphene field-effect transistor (gFET) biosensor design, which exploits the Spike-ACE2 interaction, essential for infection. Extensive computational analyses show that a chimeric ACE2-Fc construct mimics the native receptor dimer. ACE2-Fc functionalized gFET allows in vitro detection of trimeric Spike, with a limit of detection (LOD) of 20 pg/mL. Our miniaturized POC biosensor successfully detects all prominent virus variants in both isolated viruses and patient's clinical swabs with a LOD of 65 cps/mL. ga1 Highlights: A highly sensitive, rapid and variant-robust point-of-care (POC) device for SARS-CoV-2 detection is presented. Detection of the VOC B.1.610, Alpha, Beta, Gamma, Delta and Omicron (BA.1, BA.2, BA.4, BA.5, BA.2.75 and BQ.1) is reported. ACE2-Fc chimera shows improved stability for viral detection in functionalised gFET. ACE2-Fc_gFET has a LOD of 20 pg/mL for recombinant Spike protein and 65 cps/mL for swab samples of SARS-CoV-2.